2016
DOI: 10.3138/ptc.2015-38lhc
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Exercise on Functional Mobility in Adults with Cerebral Palsy: A Systematic Review

Abstract: Purpose: We identified evidence evaluating the effect of exercise on functional mobility in adults (aged 18 y or older) with cerebral palsy (CP). Method: An exhaustive search was conducted using the electronic databases PubMed, MEDLINE, CINAHL, PsycINFO, SPORTDiscus, and Cochrane Database of Systematic Reviews from the earliest available evidence (1975) to the present (January 2016) for studies whose participants were ambulatory adults with CP receiving conservative treatment to address functional mobility li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Early-onset motor decline not only negatively affects function in daily life but also makes it difficult to form social connections, which can lead to psychological decline and social isolation (3). Studies on life expectancy in CP have reported that the increase in the survival rates of adults with CP has led to growth in their total population, including those with minor and severe disabilities (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Early-onset motor decline not only negatively affects function in daily life but also makes it difficult to form social connections, which can lead to psychological decline and social isolation (3). Studies on life expectancy in CP have reported that the increase in the survival rates of adults with CP has led to growth in their total population, including those with minor and severe disabilities (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to further improve the care and rehabilitation of patients with CP, new approaches have been applied recently, specifically the use of games within the interventions’ schemes (e.g., Tatla et al, 2013 ; Lawrence et al, 2016 ; Cooper and Williams, 2017 ; Ravi et al, 2017 ). Due to their design elements, games can offer rewarding and engaging experiences that can be shared with other players in the form, for instance, of “achievements” (e.g., number of points, ranking) (see Boyle et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the interactive nature of the games enables constructive, situational, and experiential learning opportunities, enhanced by active game experimentation ( Squire, 2008 ; Hainey et al, 2011 ; Girard et al, 2012 ). For these reasons, games have been employed as a way of promoting the engagement and participation of patients with CP in their rehabilitation programs (e.g., Tatla et al, 2013 ; Bonnechère et al, 2014a ; Lawrence et al, 2016 ; Cooper and Williams, 2017 ; Ravi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found six additional articles that defined FM. [6][7][8][9][10][11] Although few, and none presenting a formal definition of FM, all shared with the Forhan and Gill description, the idea that FM is a subject's ability to move in his or her environment, focused on gait, balance, and transfers, in order to accomplish functional tasks of everyday living (e.g., walking in a corridor at work, climbing stairs at home, getting up from bed, rising from a chair to answer the phone, standing, and bending to reach an object). Therefore, we assume this as the most suitable definition to be in the context of this systematic review.…”
Section: Methodsmentioning
confidence: 99%
“…To check the adequacy of our choice, we matched the adopted definition with those founded in a Medline/PubMed electronic open search, conducted to look for a formal definition of FM (regardless of the research topics). We found six additional articles that defined FM . Although few, and none presenting a formal definition of FM, all shared with the Forhan and Gill description, the idea that FM is a subject's ability to move in his or her environment, focused on gait, balance, and transfers, in order to accomplish functional tasks of everyday living (e.g., walking in a corridor at work, climbing stairs at home, getting up from bed, rising from a chair to answer the phone, standing, and bending to reach an object).…”
Section: Methodsmentioning
confidence: 99%